Bimbingan dan Konseling Sekolah - H Kamaluddin (Jurnal Pendidikan dan Kebudayaan, 2011)
The counselor plays an important role in the education system. They are regarded as school psychology. Counseling must possess and target to expand and develop the student’s potentials. They must posses good public relations and alternative solutions to students.The counselor conducts planning, carry out the programme, monitor and evaluate, and take further actions in their counseling activities. The counselor is also responsible to provide career path to the students. To conclude, the counselor act as a problem solver to the students. The Ministry of Education has given full freedom to the counselor to develop the students’ potentials and provide effective guidance and counseling.